Uniqueness in law of solutions of stochastic differential inclusions - Lepeyev, A.N. (Інститут математики НАН України, 2007)
The paper deals with one-dimensional homogeneous stochastic differential inclusions without drift with Borel measurable mapping at the right side. We give the conditions for uniqueness in law and existence of unique in law weak solutions of the inclusions with locally unbounded right sides.